2016
DOI: 10.1590/1414-431x20165512
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and skeletal muscle dysfunction are present in healthy smokers

Abstract: Chronic exposure to cigarette smoke seems to be related to an increase of pro-inflammatory cytokines, oxidative stress and changes in muscular and physical performances of healthy smokers. However, these parameters have not yet been evaluated simultaneously in previous studies. The participants of this study were healthy males divided into two groups: smokers (n=20) and non-smokers (n=20). Inflammation was evaluated by measuring plasma levels of the cytokines IL-10, IL-6 e TNF-α, and of the soluble receptors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Three quasi-experimental studies investigated the biological effects of smoking. The results of those studies reported smokers had decreased local muscle O2Hb [ 206 ], thiobarbituric acid [ 211 ], and catalase [ 211 ] levels, an increase in inflammatory markers (sTNFR1) [ 211 ] and similar VO2 [ 206 , 211 ], lactate [ 206 ], superoxide dismutase (SOD) [ 211 ], and succinate dehydrogenase (SDH) activity [ 220 ], inflammatory cytokines (IL-6, IL-10, and sTNFR2), myoglobin concentration [ 220 ], and capillarization [ 220 ] during leg muscle exercises.…”
Section: Resultsmentioning
confidence: 99%
“…Three quasi-experimental studies investigated the biological effects of smoking. The results of those studies reported smokers had decreased local muscle O2Hb [ 206 ], thiobarbituric acid [ 211 ], and catalase [ 211 ] levels, an increase in inflammatory markers (sTNFR1) [ 211 ] and similar VO2 [ 206 , 211 ], lactate [ 206 ], superoxide dismutase (SOD) [ 211 ], and succinate dehydrogenase (SDH) activity [ 220 ], inflammatory cytokines (IL-6, IL-10, and sTNFR2), myoglobin concentration [ 220 ], and capillarization [ 220 ] during leg muscle exercises.…”
Section: Resultsmentioning
confidence: 99%
“…Spillover of inflammatory mediators produced by lung epithelial cells in response to smoking may reach the striated muscles with negative bioenergetic consequences (Fetterman et al, 2017; Madani et al, 2018). The mitochondrion, as important source of biochemical and thermal energy, is a key target for smoking toxicity, leading to reduced respiration, decreased ATP content, and increased production of free radicals in a dose- and time-dependent manner (Neves et al, 2016; Fetterman et al, 2017; Madani et al, 2018). As a consequence, smokers may present with impaired oxidative phosphorylation (as extensively reviewed by Fetterman et al, 2017).…”
Section: Peripheral Muscular Abnormalitiesmentioning
confidence: 99%
“…However, there is paucity of information regarding the effect of ambient PM 2.5 on human skeletal muscle and adipose tissue. Previous studies show that cigarette smoke leads to skeletal muscle cell damage, muscle protein breakdown 16 , skeletal muscle dysfunction 17 , and central obesity 18 . Because ambient PM 2.5 and cigarette smoke share some common patho-physiologic mechanisms like oxidative stress and inflammation, ambient PM 2.5 may have negative effects on muscle and adipose tissue in the elderly, a population susceptible to air pollution.…”
Section: Introductionmentioning
confidence: 99%